Obtención de ácido cítrico a partir de pulpa de banano maduro, utilizando el hongo aspergillus niger - Calderón, Carmen Silverio (2015)
The aim of this research was to obtain citric acid from ripe banana pulp, using the fungus Aspergillus Niger for bioconversion of reducing sugars (glucose and fructose) in citric acid. The acid fermentation is perfor¬med by inoculating the fungus in two different concentrations (2 and 3 g / L), in the substrate formed of ripe banana pulp in two concentrations (40% and 50%). The citric acid concentration is determined using the method Polyvinyl polipinolidona (PVPP) by UV-Visible spectrophotometry, reaching in treatment D (3 g / L and 50% inoculum banana pulp) value of 21.12 g / L, using 150 g / L of reducing sugar (50%) from the pulp of ripe banana, at 168 hours of fermentation. Decreasing pH (4,5 to 3,2) is a factor indicating the transformation of glucose citric acid.